Capitalisms and capitalism in the twenty-first century - Morgan, Glenn; Whitley, Richard, 1944- (Oxford : Oxford University Press, 2012)
This interdisciplinary book examines comparative business systems, institutions, and practices by looking at current developments between firms, nations, and markets in an increasingly globalized world and in the context of the recent financial crises.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Capitalism; Globalization -- Economic aspects